PENANGGULANGAN PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) DI KOTA SUKABUMI PROVINSI JAWA BARAT - Nur Handayani; Mu'min Ma'ruf; Gusti Ayu Ambarawati (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2019)
Prevention of Persons with Social Welfare Problems in Sukabumi City, West Java Province. This study aims to determine the condition of poverty in the city of Sukabumi and to find out what the Sukabumi City government is doing in poverty reduction. With qualitative descriptive methods and data collection techniques of observation, interviews, documentation then analyzed through editing, classification, tabulation and interpretation of data. The results showed that the poverty line in Sukabumi City increased by Rp26,777 in 2015 from Rp395,131 per capita per month to Rp421,908 per capita per month and the percentage of poor people in Sukabumi City in the last five years decreased. Judging from the depth index of poverty (PI) is not deep enough and seen from the poverty severity index (P2) Sukabumi City is not severe enough. This shows that the programs carried out by the Sukabumi City government are quite effective in reducing poverty. Keywords: poverty, countermeasures, Sukabumi